Electromagnetic fields : theory and applications - Khan, Ahmad Shahid; Mukerji, Saurabh Kumar (Boca Raton, FL : CRC Press, 2020)
"The proposed textbook on electromagnetic fields covers all the generic and unconventional topics including electrostatic boundary value problems involving two- and three-dimensional Laplacian fields and one- and two- dimensional Poissonion fields, magnetostatic boundary value problems, eddy currents, and electromagnetic compatibility"--
OCLC-licensed vendor bibliographic record.
Keywords: Electromagnetic fields -- Textbooks; TECHNOLOGY / Electricity; TECHNOLOGY / Microwaves